Skoðanir lækna á starfssviðum sérgreina I - Hjalti Kristjánsson; Jóhann Ág. Sigurðsson; Guðjón Magnússon; Berggren, Leif (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) Earlier studies on territories and territorial behaviour have mainly dealt with physical territories in man and animals. Recently, research has also been focused on conceptual or non-physical territoriality, based on groups with special education, professions etc. After 1970, there has been increased emphasis on health care services outside hospitals in the Nordic countries. GPs have received better pre-and postgraduate education and new health centers have been built. From that time holistic view, continuity, comprehensiveness and community based services have been the key words. Because of this development GPs have taken over more and more tasks which specialists in other fields of medicine had before. This has led to conflicts and debates about resources and groups of patients. A study was carried out in Gothenburg 1986 with the aim of developing and testing hypotheses on non-physical territoriality in health care organizations in Sweden. Similar studies were performed in the other Nordic countries, and this survey deals with the result from Iceland. A questionnaire with 65 statements and some background variables was mailed to 185 physicians in seven specialities. The total response rate was 81% ranging from 100% for GPs to 63% for pediatricians. Professional non-physical territories exist among different categories of Icelandic physicians. GPs and oto-laryngologists are usually on the strongest opposite opinion especially regarding the need to direct the flow of patients. There is also disagreement between specialities regarding who should take care of school health care, child- and maternity health care. The results will be published in further detail in four subsequent articles. Fjallað er um skoðanir lækna á skipulagningu heilbrigðisþjónustu og hugtakið huglæg vallhöslun (non-physical territorial behaviour) skilgreint í þessu samhengi. Um er að ræða samnorræna könnun þar sem sendur var út ...